Biology and population dynamics of rainbow prawn, Parapenaeopsis sculptilis (Heller, 1862), in coastal waters of Terong, Perak, Malaysia - Alsayed, Amani Abdulaziz A. (2015)
Taxonomy, morphometry, food and feeding habits, reproduction and population parameters of Parapenaeopsis sculptilis Heller 1862 in the coastal waters of Terong, Perak, Peninsular Malaysia were studied between February 2012 and January 2013. A total of 120 specimens of P. sculptilis were used for morphometric studies and they were collected from four different locations viz. Perak, Penang, Port Dickson and Malacca. The morphometric characteristics investigated include the total length, standard length, carapace length, carapace height, rostral length, second pleon segment height, sixth pleon segment length, telson length, telson width, eye wide and eye length. The morphometric study is aimed to investigate on the possibility of differences in body morphometric characteristics amongst the different P. sculptilis populations in Peninsular Malaysia waters.The result showed that all morphometric characters of P. sculptilis from four different areas in the west coast of Peninsular Malaysia were significantly (P < 0.05) different at 5% level except for CL, CH, RL and TEW (P > 0.50) not significant at 5% level. Feeding process particularly feeding items is one of the important biological characteristics for species that has aquaculture potential. The observation of the stomach contents of 360 specimens from coastal waters of Terong Perak, found only 10.14% of empty stomachs of the P. sculptilis while 89.84% of the stomachs filled up with foods. The highest percentages of full stomachs, 3/4 full, 1/2 full and 1/4 full were found in January, June, May and March respectively. The diet compositions of P. sculptilis were grouped into nine different categories viz. phytoplankton, zooplankton, mollusca, fish scales, polychaetes, appendages of crustacean, detritus, sand and unidentified items. According to the Index of Relative Importance (%IRI), the main food items of P. sculptilis graded as first rank was molluscs (64.73%), and this was followed by appendages of crustacean (17.88%), zooplankton (7.49%), detritus (2.64%), sand (2.27 %), phytoplankton (2.20%), fish scales (1.84 %), unidentified items (1.19 %) and polychaetes (0.69%). The various composition of food items proved that the P. sculptilis is an omnivorous bottom feeder. A study was also included to examine the sex ratio in the population of Terong coastal waters and the annual results for the ratio was found to be 1:3.4 (Males: Females). Consecutively, a study on the reproductive biology was carried out on 50 female individuals each month. Samples were examined monthly and the peak Gonadosomatic Index (GSI) of female P. sculptilis was very apparent during the months of April, August and October in the study area. The first sexual maturity of female was attained at a total length of 9.30 cm. The highest GSI value (5.89) was observed in April, where the females were a mature stage. The lowest GSI (0.63) was obtained in November, where the females were at an early active and immature phase. Relative condition factor (Kn) values ranged from 0.99 to 1.064 (1.013±0.005, mean ±SD). Kn values changes in various months: the highest peak was in March-April indicating the spawning period and small peaks indicated the cycle of gonadal development. A total of 3110 specimens of prawn were used for the works on the population dynamics of P. sculptilis. The estimated mean total lengths for males and females were 9.13(±0.83) and 11.96 (±2.2) cm. Length-weight relationship (LWR) parameters of both sexes was estimated at W = 0.00027TL2.80. The estimated relative growth coefficient (b) was 2.80 for the both sexes which indicated that growth pattern of P. sculptilis was negative allometric in the investigated area. Monthly length–frequency data were analysed by using FiSAT (FAO ICLARM Stock Assessment Tools) software. The von Bertalanffy growth (VBGF) parameters were estimated as asymptotic length (L) = 17.69 cm and growth coefficirent (K) = 2 yr-1. The total mortality (Z), natural mortality (M) and fishing mortality (F) were found to be 6.71, 1.77 and 4.94 yr-1 respectively. The exploitation (E) rate was calculated as E = 0.74 which is higher than optimum level of exploitation (E= 0.50). It is revealed that the status of the stock of P. sculptilis is over exploited the in the coastal waters of Terong, Perak, Peninsular Malaysia.